2006
DOI: 10.3928/01484834-20060901-06
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Development of Nursing Students: Developing Competence to Provide Spiritual Care to Patients at the End of Life

Abstract: <h4>ABSTRACT</h4> <P>Nurses spend more time with their patients than do other health care workers. Therefore, the spiritual needs of patients must be recognized as a domain of nursing care. Holism cannot exist without consideration of the spiritual aspects that create individuality and give meaning to people’s lives. The purpose of this article is to provide nursing faculty with tools that may be used to develop spiritually knowledgeable nursing students who can overcome barriers to providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…If the abstracts confirmed that the article should be included, the full article was retrieved and read for evaluation. In the final decision about which articles to review, two articles that were weak in methodology were included (Mitchell et al 2006, Rankin & Delashmutt 2006 because they gave a rich description of how students were followed up in clinical studies. In total, 10 articles were reviewed (see Figure 1 for details regarding the process of retrieving the articles).…”
Section: Evaluation Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…If the abstracts confirmed that the article should be included, the full article was retrieved and read for evaluation. In the final decision about which articles to review, two articles that were weak in methodology were included (Mitchell et al 2006, Rankin & Delashmutt 2006 because they gave a rich description of how students were followed up in clinical studies. In total, 10 articles were reviewed (see Figure 1 for details regarding the process of retrieving the articles).…”
Section: Evaluation Of Literaturementioning
confidence: 99%
“…The selection process for articles. and situations (Catanzaro & McMullen 2001, Mitchell et al 2006, Rankin & Delashmutt 2006, Hoffert et al 2007). Meyer (2003) calls it entering the journey of discovery with patients.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The literature also indicated that one focus of debate regarding spiritual care in nursing education has been on teaching content and methods (Stoll 1979, Catanzaro & McMullen 2001, van Leeuwen & Cusveller 2004, Mitchell et al 2006, McSherry et al 2008 as well as the organising of curricula (Narayanasamy 1999, Highfield et al 2000, Lemmer 2002, Ross 2006. Recently, research in many areas of spiritual care has increased, but there is very limited work from the student perspective on learning to provide spiritual care (Hoffert et al 2007, Wallace et al 2008, an area that needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…What to teach about the spiritual domain, how to facilitate students to recognise spiritual cues and to learn spiritual assessment and care giving strategies, and how to assess student learning outcomes remain a concern to nursing educators (Narayanasamy 1999b, Lemmer 2002, Pesut 2003, Callister et al 2004, Mitchell et al 2006, Hickey et al 2008. With the increased focus on spirituality, nurse educators must teach the art as well as science of spiritual care (McSherry & Ross 2010).…”
Section: Introductionmentioning
confidence: 99%